The Politics of Housing in (Post-)Colonial Africa: Accommodating workers and urban residents - Barker-Ciganikova, Martina,Rüther, Kirsten,Waldburger, Daniela,Bodenstein, Carl-Philipp (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2020)
Abstract: Housing matters, no matter when or where. This volume of collected essays on housing in colonial and postcolonial Africa seeks to elaborate the how and the why. It concentrates on analyzing housing in its multifacetedness, be it a lens to offer insights into complex processes that shape societies be it a tool of empire to exercise control over private relations of inhabitants or be it a means to create good, obedient and productive citizens
10.1515/9783110601183
Keywords: Aufsatzsammlung; (thesoz)Afrika; (thesoz)Raumplanung; (thesoz)Stadtentwicklung; (thesoz)Wohnen; (thesoz)Wohnungspolitik; (thesoz)Stadtplanung; (thesoz)Segregation; (thesoz)Kolonialismus; (thesoz)Postkolonialismus; (Zielgruppe)Fachpublikum/ Wissenschaft; (BISAC Subject Heading)HIS001000; (BISAC Subject Heading)HIS037030: HIS037030 HISTORY / Modern / General; (BISAC Subject Heading)HIS054000: HIS054000 HISTORY / Social History; (BIC subject category)HBJH: African history; (BIC subject category)HBLL: Modern history to 20th century: c 1700 to c 1900; (BIC subject category)HBTB: Social & cultural history; empire; disciplining; citizens; development policies; (BIC subject category)HBLW3: Postwar 20th century history; from c 1945 to c 2000; Stadtentwicklung; Wohnen; Kolonialismus; Postkolonialismus; Wohnungspolitik